SWI/SNF‐deficiency defines highly aggressive undifferentiated endometrial carcinoma - Basile Tessier‐Cloutier; Mackenzie Coatham; Mark Carey; Gregg S Nelson; Sarah Hamilton; Amy Lum; Robert A Soslow; Colin JR Stewart; Lynne M Postovit; Martin Köbel; Cheng‐Han Lee (Wiley, 2021)
Abstract Dedifferentiated/undifferentiated endometrial carcinoma (DDEC/UEC) is an endometrial cancer characterized by the presence of histologically undifferentiated carcinoma. Genomic inactivation of core switch/sucrose nonfermentable (SWI/SNF) complex proteins was recently identified in approximately two‐thirds of DDEC/UEC. The aim of this study was to delineate the clinical behavior of SWI/SNF‐deficient DDEC/UEC in comparison to SWI/SNF‐intact DDEC/UEC. The study cohort consisted of 56 SWI/SNF‐deficient DDEC/UEC (2 POLE‐mutated), which showed either SMARCA4 (BRG1) loss, ARID1A/1B co‐loss, or SMARCB1 (INI1) loss in the undifferentiated tumor, and 26 SWI/SNF‐intact DDEC/UEC (4 POLE‐mutated). The average age at diagnosis was 61 years for patients with SWI/SNF‐deficient tumors and 64 years for SWI/SNF‐intact tumors. Mismatch repair (MMR) protein deficiency was seen in 66% of SWI/SNF‐deficient and 50% of SWI/SNF‐intact tumors. At initial presentation, 55% of patients with SWI/SNF‐deficient tumors had extrauterine disease spread in contrast to 38% of patients with SWI/SNF‐intact tumors. The 2‐year disease specific survival (DSS) for stages I and II disease was 65% for SWI/SNF deficient tumors relative to 100% for SWI/SNF‐intact tumors (p = 0.042). For patients with stages III and IV disease, the median survival was 4 months for SWI/SNF‐deficient tumors compared to 36 months for SWI/SNF‐intact tumors (p = 0.0003). All six patients with POLE‐mutated tumors, including one with stage IV SWI/SNF‐deficient tumor were alive with no evidence of disease. Among the patients with advanced stage SWI/SNF‐deficient tumors, 68% (21 of 31) received adjuvant or neoadjuvant chemotherapy (platinum/taxane‐based) and all except the patient with a POLE‐mutated tumor (20 of 21) experienced disease progression either during chemotherapy or within 4 months after its completion. These findings show that core SWI/SNF‐deficiency defines a highly aggressive group of undifferentiated cancer characterized by rapid disease progression that is refractory to conventional platinum/taxane‐based chemotherapy. This underscores the importance of accurate clinical recognition of this aggressive tumor and the need to consider alternative systemic therapy for these tumors.